Essentials of Chinese Medicine Volume 2 - Liu, Zhanwen (Springer London : Imprint: Springer, 2009)
The modern medical model is gradually shifting from one of biomedicine to one that integrates practices from the physiological, psychological, sociological and medical fields. This growing recognition that people, the environment, ecological conditions and society are all aspects of a united whole has given rise to an emergence of alternative medicine and therapies, many of which are borrowed from traditional Chinese medicine. Volume Two presents the therapeutic methods of Chinese Medicine, including the basic methods and theories of acupuncture and moxibustion. 84 Chinese herbal formulas and 6 associated formulas commonly used in clinical practice are explained and illustrated, providing the reader with a thorough introduction to the use of herbs in Chinese Medicine.